A Physics-Based Modelling and Control of Greenhouse System Air Temperature Aided by IoT Technology - Ayoola Faniyi, Beatrice; Luo, Jerry (Cranfield University, 2023)
25th May, 2022 data set. The data contain the Solar irradiance, windspeed and outdoor temperature
Keywords: 'greenhouse environment'; 'energy model'; 'greenhouse climate'; 'energy minimisation'; 'control algorithm'; 'IoT control-based greenhouse'